Improving Indonesian Language Learning Activities Using Audiovisual Media at First Grade Students in SDN 36 Sungai Ambawang - Dalyunah Dalyunah (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2019)
The purpose of this study was to analyze the ability of teachers to carry out Indonesian language learning using audiovisual media in first-grade students of SDN 36 Sungai Ambawang and describe learning activities in learning Indonesian by using audiovisual media on grade I students at SDN (State Elementary School) 36 Sungai Ambawang. The research method used in this study is discrete. The subjects of this study were teachers as researchers in class I, and first-grade students at SDN 36 Sungai Ambaang, totaling 19 students, eight women, and 11 men. The procedure of conducting Indonesian language learning research uses audiovisual media through four stages, namely: a) planning, b) implementation, c) reflection, and d) evaluation. Data collection techniques used are direct observation techniques, with data collection tools in the form of observation sheets. The results showed an increase in the ability of teachers to prepare plans for implementing learning and carrying out learning in Indonesian language lessons using audiovisual media in first-grade students of SDN 36 Sungai Ambawang, and increased activity in learning Indonesian by using audiovisual media in first-grade students of SDN 36 Ambawang River physical activity in cycle I 70% increased in value in cycle II 94%, mental activity increased, cycle I 54.54% and cycle II, emotional activity in from 75% in cycle I to 95.45% in cycle II.